2006
DOI: 10.3171/foc.2006.20.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Cowden disease and Lhermitte–Duclos disease: an update

Abstract: Object Cowden disease is a rare autosomal-dominant phacomatosis and cancer syndrome that is associated with Lhermitte–Duclos disease (LDD), also called dysplastic cerebellar gangliocytoma. Methods In this review the authors summarize the additions to the literature during the past 5 years, with emphasis on new case reports and advances in imaging and molecular biology. Adult-onset LDD is now considered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 42 publications
0
45
0
8
Order By: Relevance
“…[1] The incidence is very less, 5 per million per year and approximately 222 cases of LDD have been reported in medical literature till now. [4] The age of onset of symptoms may be at any, but most commonly manifests in the third and fourth decades of life. [5] There is neither gender predilection & nor any apparent geographical pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The incidence is very less, 5 per million per year and approximately 222 cases of LDD have been reported in medical literature till now. [4] The age of onset of symptoms may be at any, but most commonly manifests in the third and fourth decades of life. [5] There is neither gender predilection & nor any apparent geographical pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Дана група захворювань має загальну назву PTEN hamartoma tumor syndromes (PTEN-асоційовані синдроми з пухли-нами і гамартомами). До них, крім синдрому Баньяна -Райлі -Рувалкаба, належать синдром Ковдена (множинні гамартоми шкіри, слизових оболонок, внутрішніх органів і залоз) і Лермітт -Дуклос (диспластична гангліоцитома мозочка) [35,36]. Ген PTEN кодує білок-супресор росту пухлин, який діє на фермент фосфоінозитид-3-кіназу, який бере участь в регуляції клітинного циклу, ангіогенезу і клітинної проліферації [37].…”
Section: N¹ 4(82) 2016unclassified
“…[1][2][3] Lhermitte-Duclos disease is a rare entity and about 220 cases have been reported till 2006. [4] We present an adult patient with medulloblastoma with suspicion of abnormal folia thickening masquerading as Lhermitte-Duclos disease. Our review of literature showed only two such case reports of medulloblastoma in children.…”
Section: Introductionmentioning
confidence: 98%